2019
DOI: 10.1186/s13018-019-1131-z
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a simplified core stabilization program (TRICCS—Trivandrum Community-based Core Stabilisation) for community-based intervention in chronic non-specific low back pain

Abstract: BackgroundChronic low back pain is a common public health problem all over the world. Conservative therapy is prescribed as the initial treatment strategy in chronic low back pain. The cornerstone of conservatism in back care is core muscle strengthening. However, exercises prescribed for the purpose are manifold and some are not easily done by patients in Asian countries. We developed an easy to adhere exercise protocol for core stabilization and tested its effectiveness in south Indian population.MethodsPros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Insbesondere Patienten mit orthopädischen Erkrankungen weisen jedoch häufig erheblich eingeschränkte sensorische, beziehungsweise propriozeptive Qualitäten auf [9,10]. Daher sollten sensomotorische Belastungsreize insbesondere zur koordinativen Ansteuerung und neuromuskulären Stabilisierung des lumbosakralen Übergangs feste Bestandteile in der Therapie orthopädischer Schadensbilder sein [11,12]. Das Training an Kraftgeräten bietet den Patienten allerdings kaum Trainingsreize, die eine Schulung der Propriozeption erlauben [13].…”
Section: Introductionunclassified
“…Insbesondere Patienten mit orthopädischen Erkrankungen weisen jedoch häufig erheblich eingeschränkte sensorische, beziehungsweise propriozeptive Qualitäten auf [9,10]. Daher sollten sensomotorische Belastungsreize insbesondere zur koordinativen Ansteuerung und neuromuskulären Stabilisierung des lumbosakralen Übergangs feste Bestandteile in der Therapie orthopädischer Schadensbilder sein [11,12]. Das Training an Kraftgeräten bietet den Patienten allerdings kaum Trainingsreize, die eine Schulung der Propriozeption erlauben [13].…”
Section: Introductionunclassified
“…Effective exercise methods for maintaining the strength and quality of the small muscle groups that contribute to the correct shape of the spine are lacking. Several studies have shown that the small muscle groups, especially the stable muscle groups in the core area of the body, are closely related to spine health [35][36][37]. This study showed poor small muscle strength among the participants, which may suggest that the coordinated development of the small and large muscles should be emphasized in future physical education reforms and adolescent health interventions.…”
Section: Discussionmentioning
confidence: 77%
“…Nevertheless, MFR combined with core exercise protocols has become quite prominent recently and studies had different protocols for comparison of the effectiveness of those interventions, such as "Core exercise versus MFR" or "MFR combined core exercises versus core exercises alone" (Meltzer et al, 2017). According to the recent systematic review, both MFR and MFR combined with other interventions seem to be effective in the management of NSLBP, yet there is no consensus between studies regarding MFR protocols, myofascial meridians, and study duration (Akhtar et al, 2017;Majeed A et al, 2019). To our best knowledge, there is no study conducted for the comparison of the effectiveness of SMFR combined with core exercises and SMFR alone on patients with NSLBP regarding pain intensity and FC.…”
Section: Introductionmentioning
confidence: 99%